Low-temperature properties of monoalcohol glasses and crystals - Ramos, M.A.; Hassaine, M.; Kabtoul, B.; Jiménez-Riobóo, R.J.; Shmyt’ko, I.M.; Krivchikov, A.I.; Sharapova, I.V.; Korolyuk, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We review and jointly discuss both earlier and recent experiments conducted by us on simple aliphatic glass-forming monoalcohols at low temperatures, including specific heat, thermal conductivity, Brillouin scattering and x-ray diffraction experiments. The family of simple monoalcohols constitutes an interesting model system to explore different relevant issues concerning molecular glass-forming liquids, low-temperature universal proper-ties of glasses, and even the glass transition phenomenon itself. More specifically, we discuss the role played by the molecular aspect ratio in vitrification/crystallization kinetics, the reported appearance of particular cases of polymorphism (in ethanol) and polyamorphism (in butanol), and especially the influence of position isomerism and the location of the hydrogen bond on the lattice dynamics and hence on the low-temperature universal prop-erties of glasses.